An improve sterilization process to increase palm oil extraction rate. - Ariffin, Abdul Azis (2006)

(untitled)
The equilibrated high steam pressure will maximize all chemical activities in the fruit bunches during the sterilization process. The high steam temperature efficiently catalyses hydrolysis processes of binding carbohydrate, proteins but not oil. The steady high pressure/temperature ensures shorter processing time. Process allows maximum hydrolysis of binding sugar molecule to allow complete separations of fruits from the bunch, separations and maintaining the intactness of the oil bearing mesocarp cells, high water to oil ratio in the pressed fibre, increased oil recovery, production of carbohydrate enriched effluents.